Binocular Visual Field and Vision-Related Quality of Life in Patients With Hemianopia. Issue 1 (26th March 2022) - Burgos-Blasco, Barbara; Perez-Garcia, Pilar; Fernandez-Vigo, Jose I.; Benito-Pascual, Blanca; Hernandez-Garcia, Elena; Saenz-Frances, Federico; Santos-Bueso, Enrique
Abstract : Background: Hemianopias can have a severe impact on functional ability and quality of life (QoL). Binocular visual field (VF) analysis is clinically more relevant to visual function than monocular VF. The aim is to analyze the binocular VF of patients with hemianopias and its association with the monocular VF and to assess the QoL of these patients through questionnaires specifically related to vision compared with healthy controls. Methods: The case–control study included patients with hemianopias and controls. Sex, age, general history, etiology, location of the lesion, and time since the lesion appeared were recorded. Monocular VF and Esterman binocular VF were performed. VF defect, mean defect (MD), and Esterman scores were recorded. Visual Activities Questionnaire (VAQ-33) and Visual Function Questionnaire (VFQ-25) questionnaires were administered. Results: Twenty patients with hemianopia and 22 healthy controls were included. The Esterman score in homonymous hemianopia patients (n = 17) correlated with best eye MD (r = −0.62, P = 0.01), worst eye MD (r = −0.70, P = 0.002), and average MD (r = −0.68, P = 0.003). Compared with healthy control subjects, patients with homonymous hemianopia had significantly lower VFQ-25 score and in 10/12 subscales (all P < 0.001). VAQ-33 scores revealed lower overall and subscales scores with the exception of light/dark adaptation ( P = 0.08). Correlations were found between monocular and binocular VF scores and general vision (r = −0.55), peripheral vision (on both questionnaires, r-range −0.75 to 0.47), VFQ-25 and VAQ-33 overall scores (r = −0.59, −0.49 and 0.50), and glare disability (r = 0.53 and 0.67). Conclusions: Hemianopic VF defects involve a major alteration in the patients' vision-related QoL.